2022
DOI: 10.3389/fgene.2022.862264
|View full text |Cite
|
Sign up to set email alerts
|

CILP, a Putative Gene Associated With Immune Infiltration in Breast Cancer Brain Metastases

Abstract: Breast cancer (BC) is the second leading cause of brain metastases (BM), with high morbidity and mortality. The aim of our study was to explore the effect of the cartilage intermediate layer protein (CILP) on breast cancer brain metastases (BCBM). Using a weighted gene coexpression network analysis (WGCNA) in GSE100534 and GSE125989 datasets, we found that the yellow module was closely related to the occurrence of BCBM, and CILP was a hub gene in the yellow module. Low CILP expression was associated with a poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In vitro experiments showed that CILP inhibited breast cancer cell proliferation and metastasis. Further analysis revealed that CILP was associated with immune effects and T cell receptor signaling in BCBM [ 23 ]. In the context of esophageal squamous cell carcinoma (ESCC), 7 stemness-related genes, including CILP, were found to be associated with prognosis, gene mutations, and immune cell infiltration in ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments showed that CILP inhibited breast cancer cell proliferation and metastasis. Further analysis revealed that CILP was associated with immune effects and T cell receptor signaling in BCBM [ 23 ]. In the context of esophageal squamous cell carcinoma (ESCC), 7 stemness-related genes, including CILP, were found to be associated with prognosis, gene mutations, and immune cell infiltration in ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, all eight genes have known associations to different kinds of cancer (Table 2). The genes are associated with laryngeal cancer (MEOX2 [45]), cervical cancer (FGF7 [46]), oral cancer (DPT [47]), breast cancer (CILP [48]) or ovarian cancer (TMEM119 [49]) and LAMP3-positive dendritic cells are generally associated with cancer [50]. Further, both genes with increased expression in intracranial metastases (PMP2 and GLDN) have known associations with melanoma cell invasion and mutation [51,52].…”
Section: Comparison Of the Most Frequently Differentially Expressed G...mentioning
confidence: 99%
“…The relationship between CILP2 and malignant tumors has not been studied thoroughly, with few reports describing this relationship. These studies report that CILP induces breast cancer brain metastases by affecting CD4 + T immune cell function [ 11 ]. However, the exact pathway by which CILP2 plays a role in CRC, especially regarding the immune response, and its link to immune cell infiltration and immune checkpoints within the TME remain unclear.…”
Section: Introductionmentioning
confidence: 99%